Chemical assessment of the new antimicrobial peptide AP-CECT7121 - Urbizu, Lucia Paola (2009)
The emergence of multi-resistant bacteria, involves a serious therapeutic concern in clinical practice. Antimicrobial peptide (AP) CECT7121 was isolated from an environmental strain of Enterococcus faecalis CECT712, showing high in vitro efficacy against most of the pathogens recalcitrant to conventional treatments. The goals of this research work were the isolation, purification and identification by chromatography (RP-HPLC, TLC and HPLC-MS/MS) of the peptide AP-CECT7121. The BHI broth was inoculated with of an overnight culture of E. faecalis CECT7121. After incubating and chemical processes, the active compound obtained, was loaded on C18 cartridges previous to RP-HPLC analysis. AP-CECT7121 was identified as a lipophylic compound by a peak at 24 min of retention time. The same fraction was used for the aminoacidic assessment using TLC, where a sequence of six aminoacids was obtained (proline, treonine, cistine, valine, tirosine y leucine). This antimicrobial compound after HPLC-MS/MS analysis showed a low molecular weight of 910 Da. Developing of AP-CECT7121 may be a potential tool for the treatment of Human and Veterinary multi-resistant bacterial infectious diseases.